2006
DOI: 10.1111/j.1365-3040.2005.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher daytime leaf temperatures contribute to lower freeze tolerance under elevated CO2

Abstract: Elevated atmospheric CO 2 adversely affects freezing tolerance in many evergreens, but the underlying mechanism(s) have been elusive. We compared effects of elevated CO 2 with those of daytime warming on acclimation of snow gum ( Eucalyptus pauciflora ) to freezing temperatures under field conditions. Reduction in stomatal conductance g c under elevated CO 2 was shown to cause leaf temperature to increase by up to 3 ∞ C. In this study, this increase in leaf temperature was simulated under ambient CO 2 conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…Experimental results suggest that responses are most likely species-specific, but there is a mounting consensus that, for many plant species, growth under elevated CO 2 can reduce their resistance and tolerance to freezing temperatures (Repo et al 1996, Lutze et al 1998, Barker et al 2005, Bertrand et al 2007). The reduction in tolerance appears to be caused by a slowdown in low-temperature acclimation (Loveys et al 2006), which is caused by higher daytime leaf temperatures due to reduced stomatal conductance under ; after the freeze setback, the canopy development resumed but did not achieve the normal level. This is in contrast to 1996, when canopy development started very late but progressed very quickly after the leaf-out, and thus was able to achieve the normal level eventually.…”
Section: Implications Of the 2007 Spring Freeze For A Changing Climatementioning
confidence: 99%
“…Experimental results suggest that responses are most likely species-specific, but there is a mounting consensus that, for many plant species, growth under elevated CO 2 can reduce their resistance and tolerance to freezing temperatures (Repo et al 1996, Lutze et al 1998, Barker et al 2005, Bertrand et al 2007). The reduction in tolerance appears to be caused by a slowdown in low-temperature acclimation (Loveys et al 2006), which is caused by higher daytime leaf temperatures due to reduced stomatal conductance under ; after the freeze setback, the canopy development resumed but did not achieve the normal level. This is in contrast to 1996, when canopy development started very late but progressed very quickly after the leaf-out, and thus was able to achieve the normal level eventually.…”
Section: Implications Of the 2007 Spring Freeze For A Changing Climatementioning
confidence: 99%
“…Prior studies that have attempted to determine the impact of a combination of elevated CO 2 and/or temperature on cold hardening in evergreens have largely focused on freezing tolerance, with contrasting results. Open-top chamber experiments showed that a combination of elevated temperature and CO 2 both delayed and impaired freezing tolerance of P. menziesii seedlings (Guak et al, 1998) and evergreen broadleaf Eucalyptus pauciflora seedlings (Loveys et al, 2006) but did not affect freezing tolerance of mature P. sylvestris (Repo et al, 1996). A recent field experiment examining mature trees revealed that Larix decidua, but not Pinus mugo, exhibited enhanced freezing damage following six years of exposure to combined soil warming and elevated CO 2 (Rixen et al, 2012).…”
mentioning
confidence: 99%
“…The measurements of gas exchange indicated that stomata were closed to a greater degree in plants cold acclimated under an elevated CO 2 level, which, according to Loveys et al (2006), may cause a decrease in freezing tolerance through an increase in daytime leaf temperature. Furthermore, no increase in net photosynthesis rate was observed, which excludes the increased growth rate connected with higher photosynthetic productivity as a possible reason for the lower effectiveness of CA at elevated CO 2 as suggested by Dhont et al (2006).…”
Section: Discussionmentioning
confidence: 99%